Governance of Higher Education in the Arab World and the Case of Tunisia - El Amine, Adnan (International Higher Education, 2019)
Public universities in the Arab world have suffered from what might be called a political model of governance. This model involves the subordination of universities to political influence, from top to bottom as well as horizontally. It leads to the closing of minds, the undermining of knowledge production, and limiting the ability of universities to bring about social change. The exception to this dominant model in the Arab world is Tunisia, which, not coincidentally, has also been the only exception to the failure of the “Arab Spring,” continuing on the path of democracy and progressive reform despite some setbacks.